Diaconia against Poverty and Exclusion in Europe: Challenges - Contexts - Perspectives - Eurich, Johannes (Veröffentlichungen des Diakoniewissenschaftlichen Instituts an der Universität Heidelberg, 2013)
Poverty and exclusion are rising challenges in all European countries. Christian welfare organisations such as Diaconia have been committed to working against poverty and marginalisation since many years. However, a change of the structures which cause poverty is often not accomplished. Poor people remain in dependent situations and do not really participate in society. What are the main challenges to diaconal institutions combating poverty and exclusion? Which innovations are necessary within diaconia and civil society in order to meet future challenges? With contributions from all over Europ